Antimycobacterial and Anti-inflammatory Mechanisms of Baicalin via Induced Autophagy in Macrophages Infected with Mycobacterium tuberculosis - Zhang, Qingwen; Sun, Jinxia; Wang, Yuli; He, Weigang; Wang, Lixin; Zheng, Yuejuan; Wu, Jing; Zhang, Ying; Jiang, Xin (Frontiers in Microbiology, 2017)
Tuberculosis (TB) remains a leading killer worldwide among infectious diseases and the effective control of TB is still challenging. Autophagy is an intracellular self-digestion process which has been increasingly recognized as a major host immune defense mechanism against intracellular microorganisms like Mycobacterium tuberculosis (Mtb) and serves as a key negative regulator of inflammation. Clinically, chronic inflammation surrounding Mtb can persist for decades leading to lung injury that can remain even after successful treatment. Adjunct host-directed therapy (HDT) based on both antimycobacterial and anti-inflammatory interventions could be exploited to improve treatment efficacy and outcome. Autophagy occurring in the host macrophages represents a logical host target. Here, we show that herbal medicine, baicalin, could induce autophagy in macrophage cell line Raw264.7 and caused increased killing of intracellular Mtb. Further, baicalin inhibited Mtb-induced NLRP3 inflammasome activation and subsequent inflammasome-derived IL-1β. To investigate the molecular mechanisms of baicalin, the signaling pathways associated with autophagy were examined. Results indicated that baicalin decreased the levels of phosphorylated protein kinase B (p-Akt) and phosphorylated mammalian target of rapamycin (p-mTOR) at Ser473 and Ser2448, respectively, but did not alter the phosphorylation of p38, JNK, or ERK both in Raw264.7 and primary peritoneal macrophages. Moreover, baicalin exerted an obvious inhibitory effect on nuclear factor-kappa B (NF-κB) activity. Finally, immunofluorescence studies demonstrated that baicalin promoted the co-localization of inflammasome with autophagosome may serve as the underlying mechanism of autophagic degradative effect on reducing inflammasome activation. Together, baicalin definitely induces the activation of autophagy on the Mtb-infected macrophages through PI3K/Akt/mTOR pathway instead of MAPK pathway. Furthermore, baicalin inhibited the PI3K/Akt/NF-κB signal pathway, and both autophagy induction and NF-κB inhibition contribute to limiting the NLRP3 inflammasome as well as subsequent production of pro-inflammatory cytokine IL-1β. Based on these results, we conclude that baicalin is a promising antimycobacterial and anti-inflammatory agent which can be a novel candidate for the development of new adjunct drugs targeting HDT for possible improved treatment.